Genetic Susceptibility to Lupus: New Insights from fine mapping and genome-wide association studies - Harley, Isaac T.W. (2009)
Genome-wide association studies and fine mapping of candidate regions have rapidly advanced our understanding of the genetic basis of systemic lupus erythematosus (SLE or lupus). More than 20 robust associations have now been identified and confirmed, and have provided insights at the molecular level that refine our understanding of the involvement of processes involved in the host immune response. In addition, genes with as yet unknown roles in SLE pathophysiology have been identified. These findings provide new routes toward improved clinical management of this complex disease.